Effect of stochastic modulation of inter-pulse interval during stimulated isokinetic leg extension - Efe Anil Aksöz; Marco Laubacher; Stuart Binder-Macleod; Kenneth J. Hunt (PAGEPress Publications, 2016)
Recumbent cycling exercise achieved by functional electrical stimulation (FES) of the paralyzed leg muscles is effective for cardiopulmonary and musculoskeletal conditioning after spinal cord injury, but its full potential has not yet been realized. Mechanical power output and efficiency is very low and endurance is limited due to early onset of muscle fatigue. The aim of this work was to compare stochastic modulation of the inter-pulse interval (IPI) to constant-frequency stimulation during an isokinetic leg extension task similar to FES-cycling. Seven able-bodied subjects participated: both quadriceps muscles were stimulated (n = 14) with two activation patterns (P1-constant frequency, P2-stochastic IPI). There was significantly higher power output with P2 during the first 30 s (p = 0.0092), the last 30 s (p = 0.018) and overall (p = 0.0057), but there was no overall effect on fatiguability when stimulation frequency was randomly modulated.